PENGARUH MANAJEMEN LABA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY: VARIABEL ANTESEDEN DAN VARIABEL MODERASI - Gita Mustika; Ria Nelly Sari; Al Azhar L (Department of Accounting-Faculty of Economic and Business (FEB), 2015)
The purpose of this study is to examine the effect of audit quality on earningmanagement and the effect of earning management on the corporate social responsibilitydisclosure. In addition, this study also examine moderating role of accounting complexity andeffectiveness of audit committee on relationship between earning management and corporatesocial responsibilty disclosure. The population in this study are manufacturing companieslisted in Indonesia Stock Exchange for the 2013 financial year and purposive sampling is usedas sampling method. Sample in this study is 60 manufacturing companies. This study usessecondary data which is obtained from company’s annual report. Statistical method used isStructural Equation Model (SEM) based on Partial Least Square (PLS). The result prove thataudit quality negatively affect the earning management, and earning management positivelyaffect the corporate social responsibility disclosure. The result also prove that accountingcomplexity and effectiveness of audit committee weaken the effect of earning management oncorporate social responsibilty.DOI: 10.15408/akt.v8i3.2775